Numerical Analysis of the Coal Mixture Composition Effects on Combustion and Gas Emissions in CFB Boiler - Santoso, Santoso; Fauzun, Fauzun (Master Program in Mechanical Engineering, Gunadarma University, 2024)
The combustion system in the CFB boiler had a high complexity, in order to identify and understand the combustion process that occurs in the CFB boiler, CFD analysis was applied. This study was conducted to analyze the combustion and gas emissions produced in a CFB boiler with several variations of coal mixture. Coal particles injected into the furnace were modeled with DPM, specifically the Euler-Lagrange approach. The coal used came from two coal mining industries and mixed with the percentages of 20% : 80%, 30% : 70% and 40% : 60%. The amounts and conditions of combustion air and coal had been determined. The simulation process in the CFB boiler was carried out at a maximum load (110 MWe) without involving bed material. The results showed that the energy and combustion temperature produced in the mixture of 20% : 80% reached the highest value, the mixture of 40% : 60% produced the highest concentration of H2O and produced the lowest concentrations of CO2, O2, NO and SO2. On the other hand, the distribution of pressure and gas velocity had relatively the same value in each mixture. This could be caused by the characteristics of coal mixture, the amount of air and coal injected, and the absence of bed material.